The Measurement of joint punishment - Wysoczyńska, Małgorzata (Acta Universitatis Lodziensis. Folia Iuridica, 2012)
The dimension of (measurements of) joint punishment presents important problem, for defendants and judges, for its obligatory voting beholden <oblige>, when premises get with article 85 k.k. So, all attempts of references are notable for this problem, particularly, attempts which have been undergone by legislator in this purpose taken in order to delete numerous interpretation doubts. Content of regulation of chapter IX of Polish penal code, but particularly, article 86 k.k. and 89 k.k. were taken into consideration. Hence, chosen jurisdictions of the Supreme Court and literature concerning this regulation were analysed, as these regulations have important meaning within last months. Passage of time entitles to these first estimates of changes.